HERMAFRODITISME DAN FEKUNDITAS I KAN BAJI-BAJI (Grammoplites scaber (Linnaeus, 1758)) (FAMILI PLATYCEPHALIDAE) DI PERAIRAN PANTAI MAYANGAN, JAWA BARAT |Hermaphroditisme and Fecundity of Rough Flathead (Grammoplites scaber (Linnaeus, 1758)) (Family Platycephalidae) in Mayangan Coastal Waters, West Java] - Ivana Yuniarti; M. F. Rahardjo; Yunizar Ernawati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2005)
Grammoplites scaber which is observed are catched by hauled gear (seine nets, gill net) from Mayangan Coastal Waters, West Java ai .june-November 2003. Hermaphroditism is observed by histological method. Result of histology show that protandrous hermaphroditism is occnred in some of specimen. Fecundity is counted by gravimetric method. Fecundity of G. scaber does not have a strong relationship with total length and total weight of the fish.